Validity of self-reported number of teeth in middle-aged Finnish adults: the Northern Finland Birth Cohort Study 1966 - Toni Similä; Pentti Nieminen; Jorma I. Virtanen (BMC, 2018)
Abstract Background We examined the validity of self-reported number of teeth in middle-aged adults by using representative cohort data to compare corresponding self-reported and clinical values. Methods This validity study is part of the representative 46-year-old follow-up of the Northern Finland Birth Cohort 1966 (NFBC1966) Study. Mailed questionnaires (n = 5950) requested information on self-reported number of teeth and background variables (education, tooth brushing and smoking), while clinical oral health examinations (n = 1891) assessed the number of teeth (the 'gold standard'). The main analyses compared the self-reported and clinical values for the number of teeth in 1669 participants. Scatterplot and Bland-Altman plot served for visual analyses, and alternative correlation coefficients (Pearson, Spearman, intraclass) for numerical comparisons separately for men and women, with stratification according to background variables. Results The clinical assessment revealed that the mean value for the number of teeth was 27.46 (SD = 2.38), while the corresponding value based on self-reported information was 27.48 (SD = 2.78). According to the Bland-Altman plot, the mean difference between the clinical and self-reported values was − 0.02 (95% limits of agreement, LoA: − 3.37 to 3.32). The observed ranges of intraclass correlation coefficients (ICC) among men and women were 0.72 to 0.95 and 0.72 to 0.85, respectively, depending on the background variables. Conclusions Self-reported number of teeth in middle-aged Finnish adults agreed closely with the corresponding clinical measure.